2015
DOI: 10.3389/fnhum.2015.00569
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of linear electrode array EMG for assessment of hemiparetic biceps brachii muscles

Abstract: This study presents a frequency analysis of surface electromyogram (EMG) signals acquired by a linear electrode array from the biceps brachii muscles bilaterally in 14 hemiparetic stroke subjects. For different levels of isometric contraction ranging from 10 to 80% of the maximum voluntary contraction (MVC), the power spectra of 19 bipolar surface EMG channels arranged proximally to distally along the muscle fibers were examined in both paretic and contralateral muscles. It was found that across all stroke sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…The reduction in MPF or MF on the paretic side has been report previously (16, 17). The decrease in MPF values of the paretic muscles could be due to the loss of muscle fibers and impairments in the motor unit following stroke.…”
Section: Discussionsupporting
confidence: 82%
“…The reduction in MPF or MF on the paretic side has been report previously (16, 17). The decrease in MPF values of the paretic muscles could be due to the loss of muscle fibers and impairments in the motor unit following stroke.…”
Section: Discussionsupporting
confidence: 82%
“…This finding correspond with EMG studies assessing hemiparetic biceps brachii muscles which attribute reduction in MFCV to altered motor unit and muscle fiber after stroke 36 . The measured shift may indicate an increase in the proportion of active type I fibers to type II fibers, which could result from motor unit dysfunction, preferential atrophy of type II fibers and/or a denervation-reinnervation of fibers occurring over time.…”
Section: Discussionsupporting
confidence: 87%
“…Subjects with relatively longer MU action potential duration on the affected side tended to have higher MU MFRs on the affected side compared to the less-affected sides. Previous studies have reported slower muscle fiber conduction velocities in certain, but not all muscles ( Yao et al, 2015 ; Conrad et al, 2017 ), and longer MUAP durations on the affected side post-stroke using intramuscular EMG ( Lukács, 2005 ). Lower firing rates on the affected side have been reported when comparing firing rates recorded at the same absolute force on both sides, using intramuscular ( Gemperline et al, 1995 ; Chou et al, 2013 ) and surface EMG decomposition techniques ( Suresh et al, 2011 ; Hu et al, 2012 ; Li et al, 2015 ).…”
Section: Discussionmentioning
confidence: 93%